2017
DOI: 10.1002/joec.12061
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Work Values Across Four Nations

Abstract: Work values are important factors in career counseling and development. The purpose of this study was to test the measurement invariance of Terada's (2009) Vocational Values Inventory, as well as compare the means of 5 latent variables across 4 nations (Japan, South Korea, the United States, and Germany) using structural equation modeling. Results indicated that the assumptions of configural, metric, and intercept invariance were satisfied across the 4 nations. A comparison of the means of the 5 latent variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The five work value types found for new-generation Chinese OCPs are not completely consistent with those commonly found in studies on different profession groups or in Western countries, including the extrinsic, intrinsic, social, altruistic, prestige-enhancing and freedom-related dimensions (Jalalkamali et al , 2016; Sillerud, 2011; Infeld et al , 2010; Lyons, 2004). The results thus represent new knowledge of the work value theory and corroborate the notion that work values may be different across professions (Rani and Samuel, 2016; Jalalkamali et al , 2016) and culture (Cogin, 2012; Roongrerngsuke and Liefooghe, 2013; van Hoorn, 2015; Lee et al , 2017).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The five work value types found for new-generation Chinese OCPs are not completely consistent with those commonly found in studies on different profession groups or in Western countries, including the extrinsic, intrinsic, social, altruistic, prestige-enhancing and freedom-related dimensions (Jalalkamali et al , 2016; Sillerud, 2011; Infeld et al , 2010; Lyons, 2004). The results thus represent new knowledge of the work value theory and corroborate the notion that work values may be different across professions (Rani and Samuel, 2016; Jalalkamali et al , 2016) and culture (Cogin, 2012; Roongrerngsuke and Liefooghe, 2013; van Hoorn, 2015; Lee et al , 2017).…”
Section: Resultssupporting
confidence: 82%
“…However, it is not the case that these six work value types can be consistently identified in all the studies. Except for using different work value measurements, the variables of generation (Jonck et al , 2017; Hansen and Leuty, 2012), cultural background (Cogin, 2012; Lee et al , 2017) and profession (Rani and Samuel, 2016; Jalalkamali et al , 2016) have been demonstrated to result in the inconsistency of work value types for different cohorts. For example, a cross-cultural study suggested a five-factor work value structure for Chinese public administration and public policy students, while also suggesting a four-factor work value structure and a six-factor work value structure for their counterparts from the United States and Malaysia, respectively (Infeld et al , 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, response category 5 was renamed category 2, category 6 was renamed 3, and category 7 was renamed 4, thus resulting in four response categories for the measurement invariance analysis. With respect to indicators of invariance, it was established that incremental changes in CFI should not exceed |0.01| (e.g., Cheung & Rensvold, 2002), |0.01| in TLI (e.g., Lee et al, 2017; Ramis et al 2015), and |0.015| in RMSEA (e.g., Chen, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…First, the study participants were limited to nurses working in hospitals in the Tohoku region of Japan. Since work values may differ by country and culture (Lee et al, 2017), caution should be exercised when applying our results to other settings. In addition, owing to the regional uneven distribution of nurses in Japan (Japanese Nursing Association, 2023), there are differences in the degree of labor shortage and wage disparities depending on the urban areas where nurses are sufficient and the rural areas where nurses are insufficient.…”
Section: Limitationsmentioning
confidence: 99%